Smart solar concentrators for building integrated photovoltaic façades. (August 2016) - Wu, Yupeng; Connelly, Karen; Liu, Yuzhe; Gu, Xiaowen; Gao, Yanfeng; Chen, George Z.
Highlights: A smart CPV suitable for use in windows has been designed. The optical behaviour of the CPV was investigated using a 3D ray tracing technique. A HPC was experimentally studied for use as the reflective layer for the CPV. Abstract: In this study a novel static concentrating photovoltaic (PV) system, suitable for use in windows or glazing façades, has been designed. The developed smart Concentrating PV (CPV) system is lightweight, low cost and able to generate electricity. Additionally, this system automatically responds to climate by varying the balance of electricity generated from the PV with the amount of solar light and heat permitted through it into the building. It therefore offers the potential to contribute to, and control, energy consumption within buildings. A comprehensive optical analysis of the smart CPV is undertaken via 3-D ray tracing technique. To obtain optimal overall optical performance of the novel smart CPV analysis has been based upon all necessary design parameters including the average reflectivity of the thermotropic reflective layer, the glazing cover dimension, the glazing cover materials as well as the dimensions of the solar cells. In addition, a hydroxypropyl cellulose (HPC) hydrogel polymer, suitable for use as the reflective thermotropic layer for the smart CPV system, was synthesized and experimentally studied.